What role does Fintech play in the banking industry today and how do banks have to adjust to it? - Zuern, Yannick (2019)
A clear definition of the term "FinTechs" does not yet exist. The combination of the words "Financial Services" and "Technology" generally refers to young companies providing technology-based systems with specialized and customer-focused financial services. FinTechs are following the trend towards digitization and personalization while driving digital progress in the financial market. In particular, they rely on customer-friendly, fast and convenient applications for user. FinTechs, however, are in the process of becoming a great challenge to traditional financial service providers such as banks, insurers and investment services, and moreover, are a great opportunity for banks to complement their services. The exact number of FinTech´s in the United Kingdom is difficult to quantify, which is partly due to the dynamics of the market. As digital progress keeps evolving, more and more companies are founded whose business models can be seen as FinTech. However, some of these companies have already ceased their activities. These new FinTech companies offer a very wide range of different business models. Many of these companies provide banking-like services, such as loan brokerage or automated financial advice. Others supplement these classic offerings with additional services, in particular in the area of payments and financial management. It is well known today that the new FinTech innovations have an enormous force on the financial sector. This progress also brings risks with it that have to be taken into consideration, prevented and managed in traditional banks business models. The UK plays a major role in the evolvement of FinTech as it is known as the world´s leading global financial services center. No other city in the world has had as many new FinTech start-ups as London, which puts a lot of pressure on regulators. The aim of this dissertation is to define the role that FinTechs play in todays banking industry and how banks have do adjust their business models to stay competitive.